Polarity-induced electronic and atomic reconstruction at NdNiO2/SrTiO3 interfaces - He, Ri; Jiang, Peiheng; Lu, Yi; Song, Yidao; Chen, Mingxing; Jin, Mingliang; Shui, Lingling; Zhong, Zhicheng (Physical review, 2020)
Superconductivity has recently been observed in Sr-doped NdNiO2 films grown on SrTiO3. Whether it is caused by or related to the interface remains an open question. To address this issue, we use density-functional theory calculation and charge-transfer self-consistent model to study the effects of polar discontinuity on the electronic and atomic reconstruction at the NdNiO2/SrTiO3 interface. We find that sharp interface with pure electronic reconstruction only is energetically unfavorable, and atomic reconstruction is unavoidable. We further propose a possible interface configuration that contain residual apical oxygen. These oxygen atoms lead to hybrids of d(z2) and d(x2-y2) states at the Fermi level, which weaken the single-band feature and may be detrimental to superconductivity.